IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI SUNGAI KAKAP, KUBU RAYA, KALBAR - Ambaryani Ambar; Sri Maryuni; Pardi Pardi (FISIP Universitas Tanjungpura, 2021)
Non-Cash Food Assistance (BPNT) is distributed in non-cash through electronic money in combo cards given to each Beneficiary Family (KPM). This assistance is determined based on the Regulation of the metamorphosis of rice assistance for the poor/prosperous rice. This study aims to see Peraturan Presiden Republik Indonesia Nomor 63 Tahun 2017, the how public policies are implemented in the field. The research was conducted in Sungai Kakap Village, Sungai Kakap District, Kubu Raya, West Kalimantan. The researcher used a qualitative approach with a descriptive type of research. Data were collected through observation, interviews and documentation. The results showed that the BPNT process in Sungai Kakap Village, Kubu Raya was not carried out optimally. Based on Mazmania and Sabatier in Tahjana (2006), three character problems can be found in the field, namely: 1) The characteristics of the problem to be solved by implementing this assistance are included in the category of problems that are difficult to handle. In addition, the poverty data used by the central government is not updated, causing new problems, the beneficiaries are not suitable; 2) The characteristics of the top down BPNT policy are formulated directly by the elite to solve a problem, even though there is a discrepancy with public conditions. 3) Non-government variables that are less coordinated because the implementor does not understand the general guidelines well. These problems have implications for the implementation of this public policy in the local community.